Hybrid organisations in global value chains: insights from Uganda's coffee sector - Mukanza, Patrick (Graduate School of Business (GSB), 2026)
Global value chains (GVCs) represent a core paradox of modern capitalism. While they generate employment opportunities in emerging economies, they also contribute to systemic inequalities, precarious labour, and environmental degradation. In response, upgrading has been proposed as a strategy for organisations to improve their position, capture value, and address social or environmental concerns. Hybrid organisations, those blending commercial and social goals, are increasingly recognised as important actors capable of challenging dominant GVC dynamics by promoting inclusive and sustainable upgrading. However, their role in African contexts remains under-researched. This study addresses this gap by investigating how hybrid organisations in Uganda's coffee sector contribute to GVC upgrading processes, by focusing on the challenges and opportunities they encounter. Uganda's coffee sector, which supports 1.8 million smallholder households and accounts for 22% of the country's export earnings, faces challenges such as price volatility, unequal power relations between local and international actors, weak infrastructure, and climate threats. These difficulties are indicative of broader global inequalities, in which, smallholder farmers in the global South commonly create value that is largely captured in the global North. Drawing on 49 interviews conducted across Uganda, the United Kingdom, and the United States, with stakeholders including farmers, hybrid organisation managers, industry experts, state actors, and international traders, the study applies a value chain analysis and examines 13 hybrid organisations using a comparative case study approach. Empirically, the findings show that hybrid organisations, positioned between smallholder farmers and international traders, contribute to economic upgrading by engaging in functional upgrading strategies such as domestic roasting, direct trade to consumer markets, and moving processing stages closer to origin. They also seek to enhance value capture at the local level by strengthening farmers' capabilities in quality control and post-harvest handling, which contributes to both product and process upgrading. In terms of social and economic upgrading, hybrids support more stable and inclusive farmer participation in the value chain by extending microloans, offering pre-financing to support farm-level investments, and providing agronomic training that strengthens farmers' agency and market positioning. Environmental upgrading is also promoted by hybrids through the adoption of climate- resilient practices, including agroforestry, composting, and soil management, which help farmers adapt to climate threats while improving long-term productivity. Yet these efforts face constraints. These include limited access to affordable finance, especially among locally embedded hybrids, and policy directions that are not well aligned with the quality-focused, socially embedded strategies many hybrids pursue. Conceptually, the study shows that hybrid organisations do not simply operate in weak institutional environments, they emerge in response to them. In areas where public or market-based support structures fall short, hybrids have emerged and filled such gaps. Their ability to combine commercial and social goals, and to work collaboratively across sectors and actors, positions them as relevant partners in efforts to promote more inclusive and sustainable upgrading in coffee value chains.